Facile production of mesoporous WO3-rGO hybrids for high-performance supercapacitor electrodes: an experimental and computational study - Samal, Rutuparna; Chakraborty, Brahmananda; Saxena, Manav; Late, Dattatray J.; Rout, Chandra Sekhar (ACS Sustainable Chemistry & Engineering, 2019)
This work explored a promising supercapacitor electrode material (WO3-rGO hybrids) synthesized via a simplistic one-pot hydrothermal synthesis route. Various analytical studies (X-ray diffraction study, Raman spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Brunauer-Emmett-Teller analysis) were employed in furtherance to explore the structural, morphological, compositional, and surface areal properties of the prepared materials. The enhancement in electrochemical supercapacitive properties were evaluated from pure hexagonal phase WO3 to the various hybrids, depending on the concentration of GO introduced into it, using cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance spectroscopy. The WG-80 composite revealed the high rise in capacitance value of 801.6 F/g overcoming the individual capacitance of rGO (71.11 F/g) and WO3 (94.22 F/g) at a current density of 4 A/g with good cycling stability (75.7%) over 5000 cycles. We have presented quantum capacitance from ab initio calculations and provided theoretical explanation from the orbital interactions.
Keywords: Density functional theory; Hydrothermal method; supercapacitor; WO3-rGO hybrids

Hydrothermal growth and humidity-dependent electrical properties of molybdenum disulphide nanosheets - Shelke, Nitin T.; Karle, S. C.; Karche, B. R. (Journal of Nanoscience and Nanotechnology, 2019)
In present investigation, we report humidity dependent electrical properties of molybdenum disulphide (MoS2) nanosheets. MoS2 nanosheets were prepared through a facile hydrothermal method with different reaction temperatures. The as-synthesized MoS2 nanosheets were characterized with XRD, SEM, TEM, and Raman spectroscopy, which confirmed successful preparation and rationality. Further, the humidity dependent electrical properties against relative humidity (RH) of these samples were carried out at room temperature. The results evinced that the sensors film fabricated with MoS2 nanosheets prepared at temperature 220 degrees C exhibited better performance compared to the nanosheets synthesized at 180 degrees C and 200 degrees C temperature. The RH sensing results exhibits highly sensitive, ultrafast response/recovery behaviour and outstanding repeatability than reported earlier. The excellent humidity sensing properties of the resultant MoS2 nanosheets was proved to be an excellent candidate for constructing ultrahigh-performance humidity sensor toward various applications.
Keywords: Humidity sensors; Hydrothermal method; Molybdenum Disulphide; nanosheets

Photoluminescence decay lifetime study of hydrothermally synthesized highly porous ruthenium-silica composite for optical dissolved oxygen sensing application - Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Pandya, Rinu; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Vanka, Kumar; Saha, Avishek; Kanawade, Rajesh (ACS Applied Nano Materials, 2026)
Pore size and surface area of photoluminescence (PL)-based transition metal composites play crucial roles in facilitating oxygen diffusion, thereby enhancing the response and sensitivity of optical dissolved oxygen (DO) sensors. In this study, we successfully applied the hydrothermal method to synthesize a porous ruthenium composite embedded in a silica matrix, demonstrating its effectiveness for optical DO sensing applications. The ruthenium-silica (Ru-Si) composites were synthesized using Ru(bpy)3 2+ and tetraethyl orthosilicate (TEOS) as precursors, with reaction temperatures ranging from 120 degrees C to 200 degrees C over a fixed duration of 4 h. The structural, morphological, and compositional characterization techniques confirmed the successful synthesis and evaluated the porosity, surface features, and chemical structure of the resulting composites. The optimized Ru-Si composite exhibited the highest porosity, characterized by a specific surface area of 996.78 m2 g- 1, and exhibited the highest decay lifetime of 8.14 mu s in deionized (DI) water, compared to other composites. Importantly, we demonstrate an excellent linear response of the synthesized Ru-Si composite to DO concentrations ranging from 2.58 to 11.16 mg L-1, with a Stern-Volmer constant of 0.12. Furthermore, a density functional theory study was conducted to investigate the electronic transitions and to elucidate the oxygen quenching mechanism of the excited Ru composite with molecular oxygen. The calculated photophysical parameters of the composite show good agreement with the experimental results. Preliminary results suggest that the synthesized Ru-Si with high pore size and surface area could be an efficient and effective composite for use in DO sensing applications.
Keywords: Hydrothermal method; opticalDO sensor; oxygen quenching; photoluminescent; ruthenium composite

Polysulfone-based polymer carbon dot membrane for optical dissolved oxygen sensing application - Kadam, Rutuja; Hattale, Gangadhar; Virole, Vishal; Pal, Sanjivani; Abraham, Athira; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Banpurkar, Arun; Kanawade, Rajesh; Saha, Avishek (Chemistry-An Asian Journal, 2026)
The precise monitoring of dissolved oxygen (DO) is essential across industrial, environmental, and biomedical applications. However, the state-of-the-art DO sensing methods often suffer from inherent limitations, which hinder their effectiveness for real-time and long-term DO monitoring. Optical DO sensing, despite its advantages, utilizes expensive metal complexes and is prone to photobleaching and slow response time. Here, we introduce a novel polymer carbon dot (PCD) as a promising candidate for lifetime-based optical DO sensing. The PCD is a metal-free, nontoxic, fluorescent, long decay-lifetime material that is synthesized through hydrothermal method. Our fluorescent PCD exhibits high emission quantum yield (24.32%), long decay-lifetime (10.43 & micro;s), and a linear response to DO concentrations ranging from 0.7 to 12.7 mg/L, with a Stern-Volmer constant of 0.1115. Further, to obtain better oxygen diffusion, high porosity, optical transparency, and high flexibility, PCD was embedded into a polysulfone matrix (PSF_PCD). The PSF_PCD membrane shows better results for the decay lifetime (9.4 & micro;s), surface energy (40.26 mN/m), and average pore diameter of 5 nm. Hence, the obtained results demonstrate the applicability of the PCD in optical DO sensors for real-time and long-term monitoring of DO levels.
Keywords: decay lifetime; dissolved oxygen; Hydrothermal method; polymer carbon dots; polysulfone-based membrane